SAT0332 ANTIBODIES AGAINST CYTOSOLIC 5'-NUCLEOTIDASE 1A IN SPORADIC INCLUSION BODY MYOSITIS: ASSOCIATION WITH CLINICAL AND MRI FEATURES. (2nd June 2020) - Dejthevaporn, R.; Shah, S.; Wastling, S.; Thornton, J.; Yousry, T.; Morrow, J. M.; Machado, P. M.
Abstract : Background: Autoantibodies directed against cytosolic 5´-nucleotidase 1A (cN1A) have been identified in sporadic inclusion body myositis (sIBM) and other connective tissue diseases. Anti-cN1A antibodies may support the diagnostic process for sIBM as well as potentially provide clues for disease pathogenesis. Nevertheless, the utility of anti-cN1A autoantibody testing in clinical practice remains unclear and requires validation. Objectives: To investigate the association between anti-cN1A antibody status and clinical and MRI features in patients with sIBM. Methods: Data for patients fulfilling European Neuromuscular Centre (ENMC) 2011 criteria for sIBM were obtained from a natural history study database. Demographic, clinical, functional assessment, and muscle MRI data in patients with sIBM who had anti-cN1A autoantibody testing were collected and analysed. Comparisons between subgroups with anti-cN1A antibody status were performed with the Mann-Whitney or Fisher's exact tests, as appropriate. Results: Forty-nine patients with sIBM had anti-cN1A autoantibody testing, of whom 17 (34.7%) were positive. Twelve patients had muscle MRI performed (seropositivity=5). Demographics, disease duration at antibody testing and overall disease pattern were closely matched in antibody positive and negative cohorts. Dysphagia was more common in the seropositive subgroup (77% vs 47%, p=0.070). Antibody positive patients were more severely affected with a trend to lower IBM functional rating scale (IBMFRS) scores (22.4±8.4 vs 26.7±6.4, p=0.09) with significantly worse ability to climb stairs (0.9±0.9, 1.7±1.1, p=0.02). On T1-weighted MRI more fatty infiltration was found in seropositive patients (Mercuri score: 3.0±0.8 vs 1.7±0.7, p=0.03). Short tau inversion recovery (STIR) hyperintensity was more conspicuous in seropositive patients (STIR extent score: 2.4±0.6 vs 1.4±0.7, p=0.04). Conclusion: There was a trend for more dysphagia and severity of dysphagia in seropositive patients. Differences in upper limb involvement were not seen according to IBMFRS and Medical Research Council (MRC) strength grades. Seropositive patients were more severely affected at the lower limb level, in terms of muscle weakness, physical function, MRI fatty infiltration and muscle inflammation. These results suggest positive antibody status is associated with a worse phenotype. These results have potential implications in clinical trials: whether antibody status influences treatment response should be assessed. Disclosure of Interests: Revadee Dejthevaporn: None declared, Sachit Shah: None declared, Stephen Wastling: None declared, John Thornton: None declared, Tarek Yousry: None declared, Jasper M Morrow: None declared, Pedro M Machado Consultant of: PMM: Abbvie, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Roche and UCB, Speakers bureau: PMM: Abbvie, BMS, Lilly, MSD, Novartis, Pfizer, Roche and UCB